2010
DOI: 10.1007/s13317-010-0014-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of receptor-based methods for detection of thyrotropin-receptor autoantibodies: a new automated third-generation immunoassay shows higher analytical and clinical sensitivity for the differential diagnosis of hyperthyroidism

Abstract: AIT patients (10.5%) were TRAb-positive with the M22-based automated assay. The percentages of TRAb positivity were lower in the same patients when the measurements were done with the second-generation method (95.1%, 18.9%, 7.0%, respectively). Conclusion: The M22-based automated immunoassay shows high functional sensitivity (0.4 mIU/l) and high diagnostic specificity, is more sensitive than the standard second-generation method and is less time-consuming and labourintensive, and is therefore the up-to-date te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Further modifications of the analytical procedures (use of receptors of different species and tissues, different types of preparation of antigenic source, washing procedures, types of tracer, etc.) allowed an improvement of analytical and clinical sensitivity of the second and third generation IMA, ranging from 0.8 IU/L to 1.5 IU/L and 96.4%-97.2%, respectively [14][15][16][17][18][19]. However, although the high clinical specificity, these assays cannot discriminate between the different types of TRAb, present in some patients with different autoimmune thyroid diseases (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Further modifications of the analytical procedures (use of receptors of different species and tissues, different types of preparation of antigenic source, washing procedures, types of tracer, etc.) allowed an improvement of analytical and clinical sensitivity of the second and third generation IMA, ranging from 0.8 IU/L to 1.5 IU/L and 96.4%-97.2%, respectively [14][15][16][17][18][19]. However, although the high clinical specificity, these assays cannot discriminate between the different types of TRAb, present in some patients with different autoimmune thyroid diseases (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…A prevalence of 9.2% was reported in 54 Singaporean patients with AIT (euthyroid and hypothyroid) which was linked to TSH-R-Ab positivity (5). Positive TSH-R-Ab levels in AIT were also observed when different assays for TSH-R-Ab measurement were validated (10,19,20,28). A recent study reported a 5.5% prevalence of positive thyroid-stimulating antibodies in 700 consecutive and unselected patients with Hashimoto's thyroiditis, while their prevalence was 68.2%…”
Section: Discussionmentioning
confidence: 99%
“…A few of the available studies focused on the hypothesis that blocking TSH-R-Ab might cause thyroid atrophy (3,8). Several studies that included hypothyroid patients showed great variability in the prevalence of elevated TSH-R-Ab, ranging from 5% to 35% (9)(10)(11). While a few surveys about euthyroid patients showed the prevalence rate between 9% and 23% (4,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, both competitive and non-competitive TRAb assays do not differentiate TBAb from TSAb [22][23][24]. However, TSHR bioassays, the sole assay variants enabling TSAb/TBAb differentiation, have not been introduced into routine laboratories widely yet, although they have proven practical usefulness despite their challenging assay design [25,26].…”
Section: Discussionmentioning
confidence: 99%